Q586B2 is a crucial virulence factor during the early stages of Trypanosoma brucei infection that is conserved amongst trypanosomatids - Stijlemans, Benoit; De Baetselier, Patrick; Van Molle, Inge; Lecordier, Laurence; Hendrickx, Erika; Romão, Ema; Vincke, Cécile; Baetens, Wendy; Schoonooghe, Steve; Hassanzadeh-Ghassabeh, Gholamreza; Korf, Hannelie; Wallays, Marie; et al. (Nature Communications, 2024)
AbstractHuman African trypanosomiasis or sleeping sickness, caused by the protozoan parasite Trypanosoma brucei, is characterized by the manipulation of the host’s immune response to ensure parasite invasion and persistence. Uncovering key molecules that support parasite establishment is a prerequisite to interfere with this process. We identified Q586B2 as a T. brucei protein that induces IL-10 in myeloid cells, which promotes parasite infection invasiveness. Q586B2 is expressed during all T. brucei life stages and is conserved in all Trypanosomatidae. Deleting the Q586B2-encoding Tb927.6.4140 gene in T. brucei results in a decreased peak parasitemia and prolonged survival, without affecting parasite fitness in vitro, yet promoting short stumpy differentiation in vivo. Accordingly, neutralization of Q586B2 with newly generated nanobodies could hamper myeloid-derived IL-10 production and reduce parasitemia. In addition, immunization with Q586B2 delays mortality upon a challenge with various trypanosomes, including Trypanosoma cruzi. Collectively, we uncovered a conserved protein playing an important regulatory role in Trypanosomatid infection establishment.